Strategies to optimise culturally appropriate perioperative care for Aboriginal and Torres Strait Islander peoples: A discussion paper - Maureen Joye; Paula Foran (Journal of Perioperative Nursing)
The disparity in health outcomes between Indigenous and non-indigenous Australians continues to increase. Barriers to accessing health care, particularly surgical treatment, contribute to health inequalities among Indigenous Australians. Despite a positive correlation between improved patient experiences and health outcomes, there is little research available on nursing interventions to improve Indigenous patients’ perioperative health care treatment.